DIGITAL DENTAL INNOVATION AND ECONOMIC EFFICIENCY: EVIDENCE FROM INTRAORAL SCANNERS AND 3D PRINTING - Al Naggar, Hesham Saleem; Nurlia, Nurlia; Al Haddad, Abdurrahman Jameel (Universitas Muhammadiyah Pontianak, 2024)
This study explores the economic implications of adopting digital dental technologies, particularly intraoral scanners and 3D printing, in enhancing cost efficiency and productivity within dental practices. The research addresses the central problem of understanding how digital innovation in dentistry contributes to broader macroeconomic efficiency and value creation in the healthcare sector. Guided by the Digital Dental Economic Model (DDEM), this paper employs a conceptual and analytical macroeconomic approach that integrates theories of endogenous growth, cost-efficiency analysis, and value chain transformation to assess the long-term economic effects of digitalization in dental services. The findings reveal that digital adoption significantly improves operational efficiency by reducing variable costs, minimizing manual errors, and increasing treatment throughput. These micro-level gains transmit into macroeconomic productivity growth, consistent with the Solow model of technological progress. However, the study also identifies asymmetric adoption patterns and labor substitution effects, particularly affecting small clinics and dental technicians, indicating the need for targeted innovation policies and re-skilling programs. Furthermore, the digital transformation of dentistry reshapes its value chain, generating new forms of interconnected economic relationships but raising ethical and data governance concerns. The analysis concludes that digital dental technologies serve as a dual catalyst for economic efficiency and structural change within healthcare systems. To sustain this transformation, policymakers should prioritize inclusive innovation, financial accessibility, and ethical digital governance. Future research should employ empirical modeling and cross-country comparative analyses to quantify digital adoption’s macroeconomic impact and evaluate policy responsiveness across healthcare economies.